Assessment of personal exposure to ozone in asthmatic children residing in Mexico City Evaluación de la exposición personal a ozono en niños asmáticos de la Ciudad de México - Matiana Ramírez-Aguilar; Albino Barraza-Villarreal; Hortensia Moreno-Macías; Arthur M Winer; Pablo Cicero-Fernández; Ma. Guadalupe Doris Vélez-Márquez; Marlene Cortez-Lugo; Juan José Sienra-Monge; Isabelle Romieu (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: A study was conducted to evaluate personal ozone exposure (O3p) among asthmatic children residing in Mexico City. MATERIAL AND METHODS: A total of 158 chil-dren were recruited from December 1998 to April 2000. On average, three O3p measurements were obtained per child using passive badges. Time-activity patterns were recorded in a diary. Daily ambient ozone measurements (O3a) were obtained from the fixed station, according to children's residence. Levels of O3a and ozone, weighted by time spent in different micro-environments (O3w), were used as independent variables in order to model O3p concentrations using a mixed-effects model. RESULTS: Mean O3p was 7.8 ppb. The main variables in the model were: time spent indoors, distance between residence and fixed station, follow-up group, and two interaction terms (overall R²=0.50, p<0.05). CONCLUSIONS: The O3w concentrations can be used as a proxy for O3p, taking into account time-activity patterns and the place of residence of asthmatic Mexican children. OBJETIVO: Realizamos este estudio para evaluar la exposición personal a ozono (O3p) en niños asmáticos de la Ciudad de México. MATERIAL Y MÉTODOS: Se incluyeron 158 niños entre diciembre de 1998 y abril de 2000. En promedio se obtuvieron tres mediciones por niño, utilizando filtros pasivos para medir O3p. Se caracterizaron los patrones de actividad y las concentraciones ambientales diarias de ozono (O3a) se obtuvieron de estaciones fijas cercanas a la residencia del niño. Los niveles promedio de O3a y las concentraciones ponderadas por el tiempo en diferentes microambientes (O3w) fueron usados como variables independientes para modelar las concentraciones de O3p, utilizando modelos de efectos mixtos. RESULTADOS: La media de O3p fue 7.8 ppb. Las principales variables en el modelo fueron: tiempo en exteriores, distancia, periodo de seguimiento y dos términos de interacción (R²=0.50, p<0.05). CONCLUSIONES: Las concentraciones de O3w pueden usarse como "proxi" de O3p, tomando en cuenta patrones de actividad y lugar de residencia.